Technical and Economic Indicators of Operation of Milk Refrigeration Centers in Guáimaro, Camagüey - Dusquier Elizalde-Rodríguez (Revista Ciencias Técnicas Agropecuarias, 2017)
As part of the studies carried out by the Department of Mechanical Engineering of the University of Camagüey, MINAG and MINAL in Camagüey province, on the optimization of collection and distribution process of cow milk, the research is performed with the objective of determining the technical - economic indicators of operation of the refrigeration centers for the reception of cow milk in Guáimaro municipality. Operation indicators for two seasons of the year (rainy and less rainy) are determined, taking into account the time balance, using the photo-timing method according to NC 34-37 and operation costs according to NC 34-38. The results obtained of productivity per hour of main time in the rainy and less rainy seasons are 207.8 and 85.06 L/h, respectively, which was influenced by the fall of the production volume in the less rainy season, affecting the productivity per hour of operation time with 175.15 and 71.84 L/h in the rainy and less rainy seasons, respectively. Specific consumption of electrical energy is 1.62 and 3.42 kW/L for rainy and less rainy seasons, respectively, being acceptable for this type of technological process. Direct operation costs amounted to 18.11 peso/h in the rainy season and 9.56 peso/h in the less rainy season, with the highest percentage being salary costs of 58.92% and electricity consumption of 41.10% in the rainy season, behaving similarly in the less rainy season. The operation costs per liter of cooled milk are 0.10 and 0.13 peso/L for the rainy season and less rainy, respectively, the difference of 0.03 peso/L is due to the decrease in milk production in the less rainy season.